Long noncoding RNA mediates enzalutamide resistance and transformation in neuroendocrine prostate cancer - Zhu, Zhe; Xuan, Wenjing; Wang, Chaohui; Li, Chancan (Frontiers in Oncology, 2024)
Prostate cancer is a malignant tumor caused by the malignant proliferation of epithelial cells, which is highly heterogeneous and drug-resistant, and neuroendocrine prostate cancer (NEPC) is an essential cause of drug resistance in its late stage. Elucidating the evolution of NEPC and the resistance process of enzalutamide, a novel antiandrogen, will be of great help in improving the prognosis of patients. As a research hotspot in the field of molecular biology in recent years, the wide range of biological functions of long noncoding RNAs (lncRNAs) has demonstrated their position in the therapeutic process of many diseases, and a large number of studies have revealed their critical roles in tumor progression and drug resistance. Therefore, elucidating the involvement of lncRNAs in the formation of NEPCs and their interrelationship with enzalutamide resistance may provide new ideas for a deeper understanding of the development of this disease and the occurrence of enzalutamide resistance and give a new direction for reversing the therapeutic dilemma of advanced prostate cancer. This article focuses on lncRNAs that regulate enzalutamide resistance and the neuroendocrine transition of prostate cancer through epigenetic, androgen receptor (AR) signaling, and non-AR pathways that act as “molecular sponges” interacting with miRNAs. Some insights into these mechanisms are used to provide some help for subsequent research in this area.